2013
DOI: 10.1177/1367549413476013
|View full text |Cite
|
Sign up to set email alerts
|

Mediating science and nature: Representing and consuming infant formula advertising in China

Abstract: Abstract:This paper analyses the representation and consumption of infant formula advertising on Chinese television, following the baby milk scare in 2008. Drawing on the concepts of 'encoding/decoding' and 'circuit of culture', the paper investigates how the Chinese dairy industry encodes the messages of food safety and quality in their advertisements and how parents decode the messages as part of their risk management strategies. The paper focuses on two moments -representation and consumption -in the 'circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…Experiences of mothers being influenced by the infant’s grandmother in a high-income country such as the United States might be dramatically different from a country with a lower income such as Pakistan [35–37]. The finding by Liu et al that mothers that had a grandmother with an education were less likely to exclusively breastfeed may have more to do with the country-specific, highly targeted infant formula advertising in China, rather than an effect of education itself [38]. Furthermore, cultural and socioeconomic differences in ethnic groups within the same country would have the potential to have different influences on breastfeeding practices.…”
Section: Discussionmentioning
confidence: 99%
“…Experiences of mothers being influenced by the infant’s grandmother in a high-income country such as the United States might be dramatically different from a country with a lower income such as Pakistan [35–37]. The finding by Liu et al that mothers that had a grandmother with an education were less likely to exclusively breastfeed may have more to do with the country-specific, highly targeted infant formula advertising in China, rather than an effect of education itself [38]. Furthermore, cultural and socioeconomic differences in ethnic groups within the same country would have the potential to have different influences on breastfeeding practices.…”
Section: Discussionmentioning
confidence: 99%
“…Regular prosecutions are mounted, through which company executives can be jailed if the company or any of its employees engages in the advertising or promotion of infant formula in breach of the regulations (Jain, 2003). In China, however, the regulations are routinely ignored (Gong & Jackson, 2013 tional, 2008). As noted in a leading industry market report, "the huge disparity in the retail value of milk formula sales between China and India is mainly due to the significant differences between their official regulatory regimes," (Euromonitor International, 2008).…”
Section: Ministry Of Internal Trade Ministry Of Radio Film and Televmentioning
confidence: 99%
“…However, only India enforces their regulations. In China, however, the regulations are routinely ignored(Gong & Jackson, 2013). In China, however, the regulations are routinely ignored(Gong & Jackson, 2013).…”
mentioning
confidence: 99%
“…As previous research has established that ‘protection’ is a salient theme in the adverts of children’s healthcare products such as infant formula (Gong and Jackson, 2013), all adverts from both data sets were viewed repeatedly to identify the ones that convey the message of ‘protection’. It was found that a significant number of adverts (26) had constructed the narrative of ‘protection’ with an underlying message of ‘risk’.…”
Section: Methodsmentioning
confidence: 99%